Synthesis of 1,2-cis-2-C-branched aryl-C-glucosides via desulfurization of carbohydrate based hemithioacetals - Kinfe, Henok H.; Mebrahtu, Fanuel M.; Manana, Mandlenkosi M.; Madumo, Kagiso; Sokamisa, Mokela S. (Beilstein Journal of Organic Chemistry, 2015)
1-C and 2-C-branched carbohydrates are present as substructures in a number of biologically important compounds. Although the synthesis of such carbohydrate derivatives is extensively studied, the synthesis of 1,2-cis-2-C-branched C-, S-, and N-glycosides is less explored. In this article a synthetic strategy for the synthesis of 1,2-cis-2-C-branched-aryl-C-glucosides is reported via a hydrogenolytic desulfurization of suitably orientated carbohydrate based hemithioacetals. 1,2-cis-2-Hydroxymethyl and 2-carbaldehyde of aryl-C-glucosides have been synthesized using the current strategy in very good yields. The 2-carbaldehyde-aryl-C-glucosides have been identified as suitable substrates for the stereospecific preparation of 2,3-unsaturated-aryl-C-glycosides (Ferrier products).
Keywords: aryl-C-glucoside; desulfurization; Ferrier product; hemithioacetal